Biodegradable nanoparticles designed for drug delivery: The number of nanoparticles impacts on cytotoxicity - Mendes, Lívia Palmerston (2018)
Nanostructured drug delivery systems are based on biocompatible and biodegradable components. Composition, size and membrane surface properties are characteristics that may influence cell viability in cytotoxicity assays. In this work, four nanostructured systems commonly used for drug delivery were prepared and cytotoxicity was evaluated on human lymphocytes and Balb/c 3T3 fibroblasts. The hemolytic potential was also investigated. Polymeric nanocapsules (NC) and nanospheres (NS), nanostructured lipid carriers (NLC) and liposomes were prepared and characterized for size, distribution, zeta potential and number per volume of the colloidal dispersion. Cell viability was evaluated, 24 and 48h, by MTT and neutral red assays (NR). Cells were incubated with each particle in eight different dilutions varying from 2.1×10 4 < /sup > to 2.1×10 < sup > 11 < /sup > particles/mL. Diameter of nanoparticles was between 130 and 200nm, all samples exhibited narrow size distribution (polydispersity index below 0.1) and zeta potential varied from -6.8 to -19.5mV. NC, NS and NLC reduced cell viability in a dilution dependent manner. For these nanoparticles, the higher number of particles induced cell death for both cell types. Liposomes did not cause loss of cell viability even at the highest number of particles. Results suggest that, depending on the kind of nanoparticle, the number of particles in the dispersion can negatively influence cell viability in pre-clinical drug development.